Pembuatan Game “Snake & Ladder Dungeon” dengan Fitur Virtual Reality - James Eklie; Rendi Kristyadi; Viny Christanti Mawardi (Jurnal Ilmu Komputer dan Sistem Informasi, 2017)
The "Snake & Ladder Dungeon" game is a 3-dimensional game that uses the Virtual Reality feature, where players are positioned as the main character who must free themselves from the dungeon where players have to climb to each floor and have to reach the last floor of the 20th floor. Players must climb up each floor, try to survive, take power ups to add player status and also finish off the enemies until the last boss to finish the game.The gameplay of this game is the player must climb the ladder to reach to the 20th floor, by shuffling the dice to get the key that works open the door to go up to the next floor, must take power ups to raise the player's status and must defeat the last boss to finish the game. This game is for Android Smartphone with VR BOX and Bluetooth Controller.